Life – Luxury of Existence - Hedžet Tóth, Cvetka (Anali PAZU, 2022)
The article Life – Luxury of Existence analyzes the message of the stories collected in the book The Third Half-Time by the author Ivanka Klopčič Casar. Among other things, The Third Half-Time speaks about the destiny of people after the end of socialism, who are today facing unemployment and hopelessness regarding the question where to go. The author brings before us concrete life stories, which all share a common thread, i.e. the human being, double-crossed by history, who willfully decides to go back to nature. This shift from Linearism as progressive process (history) to Cyclism as circular movement, the eternal recurrence (nature) is one of the basic features of the stories. The thoughts found in The Third Half-Time evince strong commitment and obligation to nature as the author reads most directly from the book of nature. This hermeneutics of the world, which grasps the world particularly through the power of the inner self, following the example of stoics, is enriched with a feeling for ethics as the most natural phenomenon, because ethics is understood as the human second nature rather than counter-nature.
Keywords: Prekmurje; Ivanka Klopčič Casar; ethics; nature; the Mura company; unemployment